Clean & high-precision graphene nanopatterning - Ferrera, Eunice Bayot (Nanyang Technological University, 2024)
In recent decades, graphene has become a central focus of research, revolutionising materials science, and applications in nanoelectronics and semiconductors with its exceptional properties. Its versatile nature renders it highly suitable for advancing next-generation electronic devices with improved performances. As research into graphene progresses rapidly, there is escalating demand for more sophisticated fabrication processes to meet the everchanging needs and specifications of various industries. This report delves into the precise patterning of graphene using the Atomic Force Microscopy (AFM) with conditioned parameters. Despite its remarkable properties, achieving complex graphene patterns with sub-nanometre resolutions remains a challenge. The effects of the electrical bias applied to the tip of the AFM and the level of surrounding humidity, on the patterning process is investigated. The results shows the optimum parameter conditions for graphene fabrication using this technique, highlighting both its limitations and contributions to advancements in graphene applications.